Analisis Penerapan Berbagai Model Pembelajaran Terhadap Materi Sejarah ASEAN Di SD - Isfa Sonia Martialiani; Tuti Istianti; Moh. Husen Arifin (FKIP, Universitas Palangka Raya, 2021)
In IPS content studies, history or history is often thought to be monotonous and tends to bore students to the study. IPS materials are derived from social sciences that are not fragmented in the realm of scientific discipline. There are some obstacles when teachers teach history materials to students at elementary school over ASEAN'S history materials in elementary school. The study aims to analyze the learning models that can be used in ASEAN history at primary school. The study uses qualitative methods using library study techniques fo r the learning models. Based on results and discussions, there were models that could be applied to ASEAN'S history materials in elementary school, the learning models raised by current teachers that matched the challenges of the 21st century,based on hots, tpack, and student creation. They include cooperative learning, jigsaw, role playing, ADDIE model, and mind mapping. This study has led to the hope that teachers as well as readers that it can be used as reference material in the studies that follow.